Hoffmannová Jana - PETR MAREŠ (Stylistyka)
The paper gives an overview of the scientific activities of the eminent Czech linguist Jana Hoffmannová, researcher at the Institute for the Czech Language of the Czech Academy of Sciences. Since the end of the 1970s Jana Hoffmannová has been mainly engaged in text linguistics and the study of verbal communication. Since the beginning of the 1990s, the spoken Czech, the style of spoken texts and the structure of dialogue have become one of the main subjects of her interest. She has published numerous papers on, for example, intertextuality in spoken communication or on the stylization of speech in literary works. Stylistic issues have been dealt with by Jana Hoffmannová in many works. She is the author of the handbook Stylistika a… (Stylistics and..., 1997), in which she describes the relationships between stylistics and other disciplines focused on text and communication. She analyzed the heterogeneity of style in contemporary literature or stylistic tendencies in academic discourse. Electronic communication is another important subject of her research.